Stress response markers in the blood of São Tomé green sea turtles (Chelonia mydas) and their relation with accumulated metal levels - Morão, Inês F.C. (2022)
Metals are persistent worldwide being harmful for diverse organisms and having complex and combined effects with other contaminants in the environment. Sea turtles accumulate these contaminants being considered good bioindicator species for marine pollution. However, very little is known on how this is affecting these charismatic animals. Sâo Tomé and Príncipe archipelago harbours important green sea turtle (Chelonia mydas) nesting and feeding grounds. The main goal of this study was to determine metal and metalloid accumulation in the blood of females C. mydas nesting in São Tomé Island, and evaluate the possible impacts of this contamination by addressing molecular stress responses. Gene expression analysis was performed in blood targeting genes involved in detoxification/sequestration and metal transport (mt, mtf and fer), and in antioxidant and oxidative stress responses (cat, sod, gr, tdx, txrd, selp and gclc). Micronuclei analysis in blood was also addressed as a biomarker of genotoxicity. Present results showed significant correlations between different gene expressions with the metals evaluated. The best GLM models and significant relationships were found for mt expression, for which 78% of the variability was attributed to metal levels (Al, Cu, Fe, Hg, Pb and Zn), followed by micronuclei count (65% - Cr, Cu, Fe, Hg, Mn and Zn), tdx expression (52% - Cd, Fe, Mn, Pb and Se), and cat expression (52% - As, Fe, Se and Cd x Hg). Overall, this study demonstrates that these green sea turtles are trying to adapt to the oxidative stress and damage produced by metals through the increased expression of antioxidants and other protectors, which raises concerns about the impacts on these endangered organisms’ fitness. Furthermore, promising biomarker candidates associated to metal stress were identified in this species that may be used in future biomonitoring studies using C. mydas’ blood, allowing for a temporal follow-up of the organisms.